Penicillium expansum toxins correlate with post-harvest fruit rot of apple (Pyrus malus L.) - Baviskar RN; Dekate HM (International Journal of Life Sciences, 2016)
Two Penicillium expansum toxins viz. patulin and citrinin were found to be associated with P. expansum rotted apples. Both toxins were detected in very high amounts. Patulin was detected up to 35 mg/kg whereas citrinin level was comparatively lesser up to 6 mg/kg of the fruit. These amounts are very high in comparison to WHO recommended tolerance level. Present research work, therefore, suggested that proper storage and sorting of apples before marketing is very necessary, so that P. expansum rotted fruits are not consumed.